REVIEW ON GELDPOLITIK de Leef H. Dierks (2022), Springer - Bagus, P. (REVISTA PROCESOS DE MERCADO, 2024)
Prof. Leef Dierks has presented a very helpful textbook on monetary policy published by the prestigious publishing company Springer. This work mainly presents the functioning and working of the European Central Bank and analyzes it against the background of orthodox theory. For Austrian monetary economists the book is valuable. Admittedly, it does not advance Austrian theory and analysis. For that, the reader is referred to Mises’ Theory of Money and Credit, Mises’ Human Action, Rothbard’s Mystery of Banking or even Huerta de Soto’s Money, Bank Credit and Economic Cycles.